Organic–Inorganic Hybrid Clusters Assembled from Phosphomolybdate Anions and Thioarylated Tetrathiafulvalenes with Diversiform Electron States and Configurations. Issue 2 (23rd December 2019) - Zhang, Shangxi; Cao, Meng; Jiang, Xinde; Xu, Sheng; Dai, Xin; Liu, Yang; Wang, Zhenxi
Abstract : A series of organic–inorganic hybrid clusters comprising thioarylated tetrathiafulvalene derivatives (A‐S‐TTFs) and Keggin‐type polyoxometalates have been prepared via proton‐induced intermolecular charge transfer or electrochemical oxidation methods, and their structural features have been intensively studied by X‐ray diffraction. The generation of co‐crystals occurs due to the flexible structure of the A‐S‐TTF and its electrostatic interaction with the polyoxometalate anions. The complexes can be divided into three types, i.e., type I, type II, and type III, which have organic/inorganic ratios of 3:1, 2:1, and 1:1, respectively. Multiple intermolecular interactions are observed between the organic and inorganic moieties, which stabilize the structures of the resulting hybrid clusters. In the clusters, Ar‐S‐TTFs are oxidized into radical cations [except in complex (TTF4)· (PMA)· (TBA), where TTF4 is presented as a +2 cation]. There are two factors affecting the packing styles and compositions of the hybrid clusters: 1) valence state of the Ar‐S‐TTF and 2) volume of the aryl groups thereon. Abstract : Thioarylated tetrathiafulvalenes (Ar‐S‐TTFs) can be oxidized into the corresponding radical cations under constant current in the presence of a Brønsted acid. The aryls rotate around the C–S bond to configure themselves according to the guests. Thus, the Ar‐S‐TTFs assemble with the guests via non‐covalent interactions to generate organic–inorganic hybrid complexes.